Contemporary thrust and emerging prospects of catalytic systems for substitute natural gas production by CO methanation. (1st March 2022) - Hussain, I.; Jalil, A.A.; Hassan, N.S.; Farooq, M.; Mujtaba, M.A.; Hamid, M.Y.S.; Sharif, H.M.A.; Nabgan, W.; Aziz, M.A.H.; Owgi, AHK
Graphical abstract: Abstract: Traditional fossil fuels emissions (mainly COx, SOx, and NOx ) have adverse effects on human health and the atmosphere. As part of the clean use of fossil fuels, substitute natural gas (SNG) appears to be one of the most promising alternatives to coal and petroleum for its high combustion heat and low CO2 emissions. SNG can be produced using the catalytic methanation of carbon monoxide (CO). Still, the lack of a competitive and robust catalytic system is a significant challenge in CO methanation technology marketing. To emphasize enhanced catalytic CO methanation, this work offers a vital understanding of the extrinsic and intrinsic interactions between catalytic gears (active metals, support materials, and promoters). A contemporary evaluation has been made of the latest developments in CO methanation catalytic systems and the optimum synergistic relationship of active metals, support materials, and promoters. The influence of various active metals, supporting materials, promoters, synthesis methods, and reaction mechanisms studies were specifically compared and clarified to design effective CO methanation catalysts. This study can serve as a critical reference, contributing to the development of well-designed and appropriate catalysts for future applications and favorable dissemination performance in the various academic and industrial sectors.